Is nudge an effective public health strategy to tackle obesity? No. (14th April 2011) - Rayner, Geof; Lang, Tim
Abstract : Adam Oliver (doi:10.1136/bmj.d2168 ) maintains that nudges may help people to make healthier choices, but Geof Rayner and Tim Lang worry that government proposals are little more than publicly endorsed marketing